THE EFFECT OF TRAINING METHOD AND MOTOR ABILITY TO POWER DOLLYO CHAGI KICK TAEKWONDO - Solissa, Jonas; Tangkudung, James A.P. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The purpose of this research is to determine the effect of plyometrics training methods and weight training methods on the explosive power of Taekwondo dollyo chagi kicks. The study was conducted to the students of physical education and health FKIP Pattimura University of Ambon in 2012. The method of this research used field experiment with factorial design 2 x 2. From the results of ANOVA test, it was found: (1) There was explosive power difference between the Chagi Dollyo kick used plyometrics method exercises and weight training method, (2) There was interaction between the training methods and motor ability to the explosive power of Taekwondo dollyo chagi kick, (3) The athletes of highÂ  motor ability there were significant differences in the increasing of explosive power dollyo chagi kick between plyometrics methods exercises and weight training methods. (4) The athletes of low motor ability there were not significant differences in the increasing of explosive power dollyo chagi kick between with weight training method plyometrics training methods.